1995
DOI: 10.1029/95jc00529
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries and oceanography off Galicia, NW Spain: Mesoscale spatial and temporal changes in physical processes and resultant patterns of biological productivity

Abstract: Abstract. The Galician shelf off NW Spain (43N ø 9W ø) exhibits mesoscale spatial and temporal changes in biological productivity associated with upwelling. Spatial heterogeneity results from local geomorphic and land-sea interactions superimposed on the large scale atmospheric processes that produce upwelling. Wind-induced upwelling events, commonly of short (i.e., week) duration, are more common in the summer than in the winter. A series of cruises, including some time series sampling, and satellite imagery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 26 publications
0
55
0
2
Order By: Relevance
“…In the western Galician shelf maximum values for this species are located in middle shelf positions, far from the coastline, in an area where upwelling influence decreases (Prego and Bao, 1997). Its preferential distribution in the western shelf is in accordance with the more episodic upwelling conditions in this area (Tenore et al, 1995). Moreover, it has been suggested that small Thalassiosira species become more important in the sediments in areas where the nutrient supply is more consistent (Abrantes, 1988).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In the western Galician shelf maximum values for this species are located in middle shelf positions, far from the coastline, in an area where upwelling influence decreases (Prego and Bao, 1997). Its preferential distribution in the western shelf is in accordance with the more episodic upwelling conditions in this area (Tenore et al, 1995). Moreover, it has been suggested that small Thalassiosira species become more important in the sediments in areas where the nutrient supply is more consistent (Abrantes, 1988).…”
Section: Discussionmentioning
confidence: 75%
“…The general hydrographical effects of upwelling off the Galician coast have been studied during the last two decades (Fraga, 1981;Fraga et al, 1982;Blanton et al, 1984;McClain et al, 1986;Tenore et al, 1995) but a detailed mesoscale description of upwelling patterns in the Galician coast has still not been considered until recently (Prego and Bao, 1997). Using the hydrodynamical and biological characteristics of upwelling, the Galician shelf waters can hypothetically be divided into two contrasting sectors south (western shelf) and north (northern shelf) of Cape Finisterre (Estrada, 1984;Tenore et al, 1995;Prego and Bao, 1997). A third hydrodynamically delimited area, the Rias Baixas, could be defined according to its characteristic positive residual circulation (Prego, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…In the Galician rias, this situation might be related to the high primary production. In fact, upwelling events are known to occur in the rias usually twice a year, namely in spring and autumn, due to the particular hydroclimatic conditions and geographical features (Tenore et al 1995;Figueiras et al 2002). This grants a priori an important food supply until autumn which might favour to recruits from summer-autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Also, off capes, upwelling can occur with a wider range of wind directions than along a relatively linear coastline (Huthnance et al, 2002). Also, it should be noted that surface seawater temperatures lower in the CFA than in the RBA is a feature that can be noticed in several published surface water temperature distributions based on field data (see Fraga, 1981;Castro et al, 1994;Tenore et al, 1995) or based on the output from ''realistic'' physical models (see Stevens et al, 2000).…”
Section: Effect Of Shelf Topography On the Surface Distribution Of DImentioning
confidence: 95%